Dental caries in children participating in a dentistry for infants program - Lemos, Letícia Vargas Freire Martins [UNESP]; Zuanon, Angela Cristina Cilense [UNESP]; Myaki, Silvio Issáo [UNESP]; Walter, Luis Reynaldo de Figueiredo (My University, 2011)
To assess the impact of the "Dentistry for Infants" early dental care program run by Jacareí County (SP) by comparing the caries of individuals participating and not participating in this program. Methods: In total, 300 children between 0 and 48 months old were assessed in the following two groups: infants not participating in the program (G1, n = 100) and infants participating in the program (G2, n = 200). Each group was further divided according to age in subgroups of 0 to 24 months and 25 to 48 months. All children were clinically assessed for carious lesions using the visual-tactile method. The data were statistically analyzed using a paired Student's t-test, Mann-Whitney test, and c 2 test at a 5% significance level. Results: There was a significant difference in the prevalence (P) and mean index of deciduous teeth (deft) (C) that were decayed, indicated for extraction and filled, and the highest values were observed in G1 (p < 0.0001). The values were as follows: PG1, 73%; PG2, 22%; CG1, 3.45 ± 3.84; and CG2, 0.66 ± 1.57. Conclusion: Participating in the program positively impacted the infants' oral health.

Avaliar o impacto na saúde bucal de crianças atendidas em um programa de atenção precoce “Odontologia para Bebês” da prefeitura do município de Jacareí (SP), por meio da comparação da experiência de cárie entre indivíduos participantes e não participantes do programa. Métodos: Foram avaliadas 300 crianças de 0 e 48 meses de idade, as quais foram divididas em 2 grupos: G1“Bebês não participantes do Programa” (n = 100) e G2 “Bebês do Programa” (n = 200). Cada grupo foi subdividido em dois, o primeiro com crianças de 0 a 24 meses, e o segundo de 25 a 48 meses. Todas as crianças receberam avaliação clínica quanto à presença de lesões de cárie (método táctil e visual). Os dados foram tabulados e analisados estatisticamente pelos testes t de Student pareado, Mann-Whitney e c2, com nível de significância de 5%. Resultados: Houve diferença estatística para a prevalência (P) e o índice índice médio de dentes decíduos cariados, com extração indicada e obturados (ceod) (C), sendo os maiores valores observados para G1(p < 0,0001). Os valores foram: PG1 (73%), PG2 (22%), CG1 (3,45 ± 3,84), CG2 (0,66 ± 1,57). Conclusão: Concluiu-se que participar do programa interferiu positivamente na saúde bucal dos bebês.
Keywords: Pediatric dentistry; Dental caries/epidemiology; Dental caries/prevention & control; Oral health; Infant; Child; Odontopediatria; Cárie dentária/epidemiologia; Cárie dentária/prevenção & controle; Saúde bucal; Lactente; Criança